Analisis Proses Indetifikasi Karakteristik Siswa di SD Negeri Empang Bahagia 3 Kota Tangerang - Magdalena, Ina; Aisyah, Nanda; Kusnadi, Devi (Lembaga Yasin AlSys, 2023)
It is important for teachers to know variables such as physical characteristics, intelligence, perceptions, gender, abilities, learning styles, which are individual differences in students to identify student characteristics. An effective and productive teaching and learning process can be planned taking into account the individual differences of students. Since students' learning rates and interests vary, these characteristics should be taken into consideration by teachers. The purpose of this study was to determine how teachers deal with individual student differences during the teaching and learning process. Qualitative research method was used in this research. According to the research findings, teachers state that individual differences are important to determine student learning characteristics. The teacher identifies individual student differences with the help of tests, homework and activities during the teaching and learning process. The teacher also stated that in order to design a teaching and learning process that is in accordance with the differences in students, students will take an active participation in learning.